2012
DOI: 10.4293/108680812x13291597715664
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Video Game “Warm-up” on Performance of Laparoscopic Surgery Tasks

Abstract: This study suggests that those who “warm-up” with select video games may have improved laparoscopic clinical task performance compared to those not engaged in “warm-up.”

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 25 publications
0
41
2
1
Order By: Relevance
“…To a lesser degree, higher PGY level was associated with better virtual procedure scores and shorter procedure time. Finally, although previous research has correlated video game exposure with laparoscopic surgical skill [25], this trend was not observed in our data. Increased gaming experience in the nonexperts was not enough to accommodate for limited arthroscopic exposure.…”
Section: Discussioncontrasting
confidence: 96%
“…To a lesser degree, higher PGY level was associated with better virtual procedure scores and shorter procedure time. Finally, although previous research has correlated video game exposure with laparoscopic surgical skill [25], this trend was not observed in our data. Increased gaming experience in the nonexperts was not enough to accommodate for limited arthroscopic exposure.…”
Section: Discussioncontrasting
confidence: 96%
“…With modern generations of orthopedic trainees being exposed to virtual reality worlds and video-gaming, we recently demonstrated that there was no correlation between video-gaming experience and gaining of competency on a VR DHS simulator (Khatri et al 2014), which is contrary to the current literature on general surgical simulators (Rosenberg et al 2005, Rosser et al 2007, Badurdeen et al 2010, Rosser et al 2012, Giannotti et al 2013). …”
Section: Discussionmentioning
confidence: 57%
“…A further four studies were case studies, two compared a technical skills practice to no practice [30,31] and two [32,33] did not contain a control group. One RCT [34] examined the effect of mental practice prior to an operation on subsequent laparoscopic performance.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five of the included studies [24,25,27,31,33] reported `pureÕ performance timedefined as the time taken to perform an assessed task. Those articles that reported duration as part of a global rating scale were not included as such studies have been discussed above.…”
Section: Studies Reporting Performance Timementioning
confidence: 99%
See 1 more Smart Citation